Bioconversion of acrylonitrile to acrylamide using polyacrylamide entrapped cells of Rhodococcus rhodochrous PA-34 - Raj, J; Prasad, S; Sharma, N. N; Bhalla, T. C (Folia microbiologica, 2010)
The nitrile hydratase (NHase) of Rhodococcus rhodochrous PA-34 catalyzed the conversion of acrylonitrile to acrylamide. The resting cells (having NHase activity) (8 %; 1 mL corresponds to 22 mg dry cell mass, DCM) were immobilized in polyacrylamide gel containing 12.5 % acrylamide, 0.6 % bisacrylamide, 0.2 % diammonium persulfate and 0.4 % TEMED. The polyacrylamide entrapped cells (1.12 mg DCM/mL) completely converted acrylonitrile in 3 h at 10 °C, using 0.1 mol/L potassium phosphate buffer. In a partitioned fed batch reactor, 432 g/L acrylamide was accumulated after 1 d. The polyacrylamide discs were recycled up to 3×; 405, 210 and 170 g/L acrylamide was produced in 1st, 2nd and 3rd recycling reactions. In four cycles, a total of 1217 g acrylamide was produced by recycling the same mass of entrapped cells.
Keywords: bakteriální proteiny; financování organizované; biotechnologie; Bacterial Proteins; Financing, Organized; Rhodococcus; akrylonitril; imobilizované buňky; Hydro-Lyases; Acrylamide; Acrylic Resins; dehydratasy; Biotechnology; Cells, Immobilized; akrylové pryskyřice; akrylamid; Acrylonitrile